Antioxidant capacities and polyphenolics of Chinese cabbage (Brassica rapa L. ssp. Pekinensis) leaves. (15th May 2016) - Seong, Gi-Un; Hwang, In-Wook; Chung, Shin-Kyo
Highlights: Outer leaf of Chinese cabbage had the highest levels of antioxidant capacities and polyphenolics. Sinapic acid showed the highest contents in Chinese cabbage leaves. Outer and inner leaves differ mainly because of their sinapic acid contents through principal component analysis (PCA). Abstract: Chinese cabbage ( Brassica rapa L. ssp. Pekinensis) is a green leafy vegetable used mainly in kimchi, salted and fermented dishes. Consumer preference for the leaf portion differs according to the type of dishes. In this study, Chinese cabbage was divided into three parts, and their antioxidant activities were investigated through in vitro assays. The total phenolic contents (TPC), total flavonoid contents (TFC), and vitamin C contents were also determined as indicators of antioxidant contents. The phenolic acids and flavonoids were separated and identified using high performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometry (LC/MS). The outer leaf had the strongest antioxidant activity with the maximum antioxidant contents, followed by the mid- and inner leaves. Principal component analysis (PCA) revealed that outer leaf is positively related to caffeic acid, p -coumaric acid, ferulic acid, and myricetin contents, whereas the mid- and inner leaves are negatively related to sinapic acid contents.